Inclusión educativa y rincón de lectura en educación inicial I en la Escuela de Educación General Básica Teniente Hugo Ortiz. Periodo 2023-2024 - Yaguache Castro, Gladys Alejandra (2024)
The inclusive education is a strategy that seeks to provide a learning environment that respects and values diversity, regardless of the students' abilities and acknowledging the existence of various materials that can facilitate inclusion, such as the reading corners. The reading corner is a pedagogical space that aims at promoting language development, it is designed to encourage kindergarten-aged students to start reading. This curricular integration paper’s main objective was to analyze the inclusive education and the reading corner at the kindergarten level at the elementary school Teniente Hugo Ortiz. It is a qualitative descriptive study that uses as instruments for the collection of information, an interview addressed to the institution's teacher and an observation sheet. This research yielded the following results: Kindergarten teachers endeavor to foster inclusive education through the use of a reading corner, despite the few materials available in the classroom, which makes it difficult to meet all the children’s needs, thus limiting them to not delving into greater virtue about the way of thinking towards an inclusive classroom. Finally, inclusive education plays a fundamental role in the teaching process and is seen as an urgent measure to be installed to make a significant change in the education system. The reading corners are educational resources that add value to inclusion, since they allow to stimulate diversity and equity in the learning environment through creativity and imagination. In addition, the teacher states that it is very important to have this space and to use appropriate methodologies that will allow all boys and girls to be involved. Keywords: Inclusive material, Reading comprehension, Imagination, Creativity, Collaborative learning, Cooperative learning.